A journey to citizenship: Constructions of citizenship and identity in the British Citizenship Test. (27th June 2013) - Gray, Debra; Griffin, Christine
<x xml:space="preserve">Abstract</x> The British Citizenship Test was introduced in 2005 as one of a raft of new procedures aimed at addressing the perceived problems of integration and social cohesion in migrant communities. In this study, we argue that this new citizenship procedure signals a shift in British political discourse about citizenship – particularly, the institutionalization of a common British citizen identity that is intended to draw citizens together in a new form of political/national community. In line with this, we examine the British Citizenship Test from a social psychological perspective to interrogate the ways in which the test constitutes identity, constitutes citizenship, and constitutes citizenship‐as‐identity. Analysis of the test and its associated documents highlights three ways in which Britishness‐as‐identity is constituted, that is, as a collective identity, as a superordinate and national identity, and finally as both a destination and a journey. These findings are discussed in terms of their implications for models of citizenship and models of identity.